High efficiency green-emitting phosphor-in-glass films for high-power solid-state laser lighting. Issue 14 (15th July 2022) - Xu, Fucai; Liang, Yueyuan; Zhang, Jiangdan; Wang, Liansheng; Xu, Li; Wang, Luhan; Liang, Xiaojuan; Yu, Ping; Xiang, Weidong
Abstract: The next generation of solid-state lighting technology driven by laser diodes (LDs) is in full development, and the way green fluorescent materials with narrow-band emission (such as β-Sialon) exert their inherent potential in laser displays and projectors has attracted public interest. In this paper, stable borosilicate glass was utilized as an inorganic binder to prepare phosphor-in-glass films (PiFs) by cosintering sapphire and β-Sialon phosphor. There was no interface reaction between the glass and the phosphor, and the phosphor was uniformly and nondestructively distributed in the composite film closely attached to the sapphire. The optimized PiFs achieved an internal quantum efficiency of 76% and a thermal conductivity of 8.6 W m −1 K −1, and a thermal diffusivity of 2.6 mm 2 s −1 demonstrated their excellent thermal stability. A beam of high-purity light with a brightness of 887 lm and a luminous efficiency of 183 lm/W was achieved under 450 nm blue LD radiation, which is the relatively superior performance by β-Sialon series luminescent materials in an LD application reported thus far. We believe that in the near future, strategies such as adjusting glass composition, improving quantum efficiency, and sample postprocessing will further improve the performance of β-Sialon phosphors with narrow-band emission to make new contributions in the field of high-quality lasers.